Keanekaragaman strain ulat grayak jagung Spodoptera frugiperda (Smith) berdasarkan marker COI dan Tpi dengan kajian kepadatan populasi di Bali: Genetic diversity of fall armyworm Spodoptera frugiperda (Smith) strains based on COI and Tpi markers with population density analysis in Bali - Monica, Dheya Cintya; Kusumah, Yayi Munara; Winasa, I Wayan (Jurnal Entomologi Indonesia, 2025)
Spodoptera frugiperda (Smith), known as fall armyworm (FAW), originating from America that devastates corn crop, causing up to 50% damage to corn crops in Bali. Molecular identification of strain diversity using mitochondrial cytochrome oxidase subunit I gene (mtCOI) and triosephosphate isomerase gene (Tpi) markers also population density monitoring are a fundamental method for monitoring, detecting and controlling these pests. This research aims to determine FAW strain based on COI and Tpi markers and their population density analysis at representative sites in Bali. This study involved several stages: samples collection; DNA extraction; amplification, visualization; Population density observation and sequencing; and data analysis. Data were analyzed using GeneStudio and BioEdit for editing and alignment, and MEGA 11 for constructing phylogenetic tree. Sequence analysis based on COIB indicated that samples from Bali comprised of 41.67% rice strains and 58.33% corn strains, with 100% of corn strain  haplotypes being h4 FAW [FL] from Florida. Based on Tpi marker, 100% of the samples were identified as corn strains with haplotypes Ca1 and Ca2. This study found that the FAW diversity in Bali consists of two strains and one haplotype based on COI (COI-R and COI-Ch4), while based on Tpi, there is only one strain  with two haplotypes (Tpi-Ca1 and Tpi-Ca2). The highest population density of FAW was observed in the Tabanan plot, with 6,8 larvae/sample unit. Early instar larvae (2–3) were predominant in 3 WAP whereas late instar larvae (4–6) were predominant in 5 WAP.